Japanese Phase 1 Study for Global Development of Anti‐TL1A Antibody PF‐06480605: A Randomized, Placebo‐Controlled, Single‐Ascending Dose Study - Kei Fukuhara; Srividya Neelakantan; Kenichi Furihata; Hirotoshi Yuasa; Nanzhi Shi; Yuichi Yamamoto; Kenneth E. Hung (Clinical and Translational Science)
ABSTRACT PF‐06480605, a fully human IgG1 monoclonal antibody targeting tumor necrosis factor α‐like ligand 1A (TL1A), has demonstrated acceptable safety and the potential as an effective treatment for inflammatory bowel disease in phase 1/2a studies. To facilitate future clinical development in Japan and China, a Japan local phase 1 study was designed in consultation with the Japan regulatory authority. In addition to fulfilling Japan regulatory requirements, this study will bring operational efficiency and speed to global and China development by evaluating PF‐06480605 in Japanese healthy adults prior to a China local phase 1 study as required by the China regulatory authority. This phase 1, randomized, double‐blind, placebo‐controlled, single‐dose escalating study investigated the safety, tolerability, immunogenicity, pharmacokinetics (PK), and pharmacodynamics of PF‐06480605 in Japanese healthy adults assigned to receive a single subcutaneous (SC) dose of PF‐06480605 150 mg (N = 6), 450 mg (first‐in‐human dose level, N = 6), or placebo (N = 4). PF‐06480605 was well tolerated and absorbed slowly with a median Tmax of 217.5 h for both 150 and 450 mg doses. Mean t1/2 was 18.4 and 19.1 days for 150 and 450 mg, respectively. Exposure parameters showed dose proportionality. No ethnic differences in PF‐06480605 PK were observed. Serum TL1A levels increased in a dose‐dependent manner. Immunogenicity was high with 100% of anti‐PF‐06480605 antibody formulation. This study satisfied the Japan regulatory requirements, while the favorable tolerability and PK of 450 mg SC in Japanese contributed to a waiver of the 150 mg SC cohort in the China local phase 1 study. NCT04269538.